2013
DOI: 10.5433/1679-0359.2013v34n6supl1p3271
|View full text |Cite
|
Sign up to set email alerts
|

Quantificação de serapilheira em diferentes áreas sob fragmentos do Parque Nacional Serra de Itabaiana, Sergipe

Abstract: A serapilheira é um componente de suma importância em um ecossistema florestal, pois responde pela ciclagem dos nutrientes. Diversos fatores podem afetar a produção de serapilheira, sendo os climáticos e a estrutura da vegetação os mais comumente investigados. O objetivo deste trabalho foi quantificar a produção de serapilheira de áreas sob fragmentos florestais em diferentes estágios sucessionais no Parque Nacional Serra de Itabaiana, em Sergipe. O experimento foi conduzido entre os meses de janeiro e dezembr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
1
5
0
1
Order By: Relevance
“…This phenomenon occurs due to a decrease in soil water content during the dry season, where some Caatinga plants lose their leaves and abort flowers and fruits as a mechanism of survival to drought. Such results corroborate with those found for Caatinga environments Costa et al (2010) and Nascimento et al (2013). Related to the aggravation of water stress, the vegetation during the drought season loses its leaves due to the seasonality of deciduous species, reducing the leaf surface and, consequently, water loss by transpiration (Santana & Souto, 2011;Costa et al, 2007).…”
Section: Areasupporting
confidence: 87%
See 2 more Smart Citations
“…This phenomenon occurs due to a decrease in soil water content during the dry season, where some Caatinga plants lose their leaves and abort flowers and fruits as a mechanism of survival to drought. Such results corroborate with those found for Caatinga environments Costa et al (2010) and Nascimento et al (2013). Related to the aggravation of water stress, the vegetation during the drought season loses its leaves due to the seasonality of deciduous species, reducing the leaf surface and, consequently, water loss by transpiration (Santana & Souto, 2011;Costa et al, 2007).…”
Section: Areasupporting
confidence: 87%
“…In the literature, there is an indication that the leaf fraction contributes the most to the formation of litter, and the percentages obtained in the Area I (86.42%) and the Area II (80.20%) were higher than other studies conducted in Caatinga areas: Costa et al (2010) reported 65%, Santos et al (2011) reported 28.90%, Barbosa (2012) reported 72.72% and Nascimento et al (2013) reported 60%.…”
Section: Production and Stock Of Littermentioning
confidence: 77%
See 1 more Smart Citation
“…According to Henriques (2016), studying the seasonality of the leaves fraction allows greater knowledge about how the vegetation behaves in relation to climatic variations, the distribution and stock of the nutrients present in the litter disposed on the forest floor, providing a better understanding of the strategies that the vegetation uses in the process of ecosystem maintenance. Nascimento et al (2013), emphasize that the production of the leaves fraction is directly linked to the reduction of precipitation along with the reduction of the photoperiod, contributing to the water stress that leads to higher deposition of this material in the most critical periods of the year. Holanda et al (2017), studying the Sítio Riachão in Pombal-PB, found that the month of April/2010 presented higher deposition of the fraction of twigs + bark, being able to be associated with high rainfall indexes that caused strong winds, allowing the dry branches in the treetops to be soaked.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Balieiro et al (2004) found no significant differences in the rates of litter deposition between species Pseudosamanea guachapele Kunth (Harms) (Legume) and Eucalyptus grandis (12.7 and 11.8 Mg ha -1 year -1 , respectively). According to some authors, there are various (biotic and abiotic) factors that influence the rates of litter deposition, such as the type of vegetation, plant species, altitude, latitude, rainfall, temperature, lighting schemes, topography, deciduousness, successional stage, water availability and soil characteristics (FREITAS et al, 2013;NASCIMENTO et al, 2013;DICKOW et al, 2012;PINTO et al, 2008;FIGUEIREDO FILHO et al, 2003).…”
Section: Introductionmentioning
confidence: 99%